PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MELALUI PENGEMBANGAN BAHAN AJAR E-BOOK FLIPBOOK BERBASIS STUDI KASUS DI MADRASAH ALIYAH NEGERI 3 MEDAN - Sari Siregar, Rosmita (Nusantara Hasana Journal, 2025)
The background of the following research is motivated by the low mathematics learning outcomes of students in class X IPA MA Negeri 3 Medan. The purpose of this research is to develop innovative teaching materials with the type of research developed by ADDIE to obtain case study-based flipbook e-book teaching materials to improve students' mathematics learning outcomes. From the results of the validation of learning design experts, the assessment percentage was 84.3%, the validation of learning media experts was 86%, and the validation of learning material experts was 78%. So it was concluded that the teaching materials developed were suitable for use. From the calculation of the t-test using SPSS, it is known that the sig value (2 tailed) is 0.000 < 0.05, so there is a significant difference between the learning outcomes of classes A and B, where the average learning outcome of students in the experimental class using the flipbook e-book (IPA-1) is 18% higher, which is 80.39 and achieves a KKM score of 70, compared to the control class (IPA-2) which still uses conventional learning methods with printed books with an average learning outcome score of 68.75 and have not reached the KKM score. It was concluded that the case study-based flipbook e-book teaching materials were effectively used.